Three new genera in the tribe Euclidieae (Brassicaceae) - Al-Shehbaz, Isan Ali; German, Dmitry (Novon, 2016)
The new monospecific genera Anzhengxia Al-Shehbaz & D. A. German, Metashangrilaia Al-Shehbaz & D. A. German, and Rudolf-kamelinia Al-Shehbaz & D. A. German are described, and the supporting data for their recognition and the characters distinguishing them from related genera of the tribe Euclidieae are discussed. The new combinations A. yechengnica (C. H. An) Al-Shehbaz & D. A. German, M. forrestii (W. W. Sm.) Al-Shehbaz & D. A. German, and R. korolkowii (Regel & Schmalh.) Al-Shehbaz & D. A. German are proposed.
Gesehen am 13.08.2020